2007
DOI: 10.1097/qad.0b013e32823ecf7f
|View full text |Cite
|
Sign up to set email alerts
|

Belief in divine healing can be a barrier to antiretroviral therapy adherence in Uganda

Abstract: Although recent data suggest high levels of adherence to expanding antiretroviral therapy (ART) programmes in resource-limited settings, the culture-specific barriers to adherence are poorly understood. In a prospective observational study, we found that 1.2% of patients discontinued ART because of a belief in spiritual healing. Spiritual beliefs should be an important part of ART adherence counselling in resource-limited settings, requiring close collaboration between HIV care programmes and religious leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 2 publications
5
72
0
Order By: Relevance
“…This ultimately may influence the extent to which they access and use unconventional treatments. In the African context, religion has a strong connotation with the traditional medical system 35, 36. Students who practice Christian faith were more likely to utilise prayer and faith healing interventions than other students who share belief in other religious denominations.…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately may influence the extent to which they access and use unconventional treatments. In the African context, religion has a strong connotation with the traditional medical system 35, 36. Students who practice Christian faith were more likely to utilise prayer and faith healing interventions than other students who share belief in other religious denominations.…”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, it was found that stigma led to non-retention in 25% of patients on ART [56]. In Uganda, it was found that 1.2% of patients discontinued ART because of a belief in spiritual healing [57]. Programs with home- and community-based services had a lower loss to follow-up rate (1-5%) compared to programs without these services (10-14%) [58-63].…”
Section: Discussionmentioning
confidence: 99%
“…The co-existence of traditional and Christian belief systems has also been described in other countries such as Uganda, Mozambique and South Africa (Edwards, 1983;Pfeiffer, 2005;Teuton et al, 2007). In sub-Saharan Africa, Christian concepts of disease, including its cause and treatment such as prayers, alongside THM have been reported for psychosis, infertility and HIV/AIDS amongst others (Adogame, 2007;Obisesan and Adeyemo, 1998;Teuton et al 2007;Wanyama et al 2007). In the latter, the belief in divine healing may even represent a barrier to antiretroviral therapy adherence (Wanyama et al, 2007).…”
Section: Attitude Of Interviewed People Towards Traditional Healing Mmentioning
confidence: 98%
“…In sub-Saharan Africa, Christian concepts of disease, including its cause and treatment such as prayers, alongside THM have been reported for psychosis, infertility and HIV/AIDS amongst others (Adogame, 2007;Obisesan and Adeyemo, 1998;Teuton et al 2007;Wanyama et al 2007). In the latter, the belief in divine healing may even represent a barrier to antiretroviral therapy adherence (Wanyama et al, 2007).…”
Section: Attitude Of Interviewed People Towards Traditional Healing Mmentioning
confidence: 99%